Melting and Evolution of Amphibole‐Rich Back‐Arc Abyssal Peridotites at the Mado Megamullion, Shikoku Basin - A. Sen; J. E. Snow; Y. Ohara; K. Hirauchi; Y. Kouketsu; A. Sanfilippo; V. Basch; Y. Harigane; M. Fujii; K. Okino; N. Akizawa (Geochemistry, Geophysics, Geosystems, 2021)
Abstract The Mado Megamullion is an oceanic core complex (OCC) in the Shikoku back‐arc basin within the Philippine Sea Plate. Mantle peridotites (serpentinized) recovered by six dredge and submersible cruises exhibit signatures of extensive deformation. Amorphous pseudomorphs after plagioclase in many of the samples, as well as plagioclase‐spinel intergrowths, are clear evidence of melt stagnation and mantle reaction. Spinels show a wide range of compositions in terms of their Cr#, Mg#, and TiO2 content. The presence of apparently magmatic high‐temperature pargasitic amphibole in veins and as replacement of clinopyroxene suggests that it may be a primary or near‐primary mineral crystallized from a hydrous melt which is unusual for abyssal peridotites. Two trace‐element populations of clinopyroxenes are in equilibrium with depleted and enriched basaltic melts, respectively. Rare‐earth element (REE) in the most depleted clinopyroxenes are modeled by 10% fractional melting except for a ubiquitous La‐Ce “kick.” Multiple models of open system melting combined with subsequent mixing of an enriched melt can explain the REE data. Broadly it appears that the peridotites underwent variable degrees of partial melting with moderate influx of enriched melts, which agrees with the other textural and chemical evidence of melt‐rock reaction and re‐fertilization. The compositions of the accumulated melts simulated by the open system models reproduce the enrichments in fluid mobile elements (Ba, U, and Pb) observed in basalts dredged from the Shikoku basin. Back‐arc basin peridotites at Mado Megamullion appear to have a unique petrographic and geochemical character that is distinct from those of peridotites exposed at the seafloor after formation from mid‐ocean ridges.